An Overview of Sexual Activity Perception Activities in Pregnant Women in Sleman Hospital - Yekti satriyandari; Sri Sulistyawati (International Journal of Health Science and Technology, 2020)
Pregnant women and their partners' perceptions of pregnancy will greatly determine their behavior in sexual intercourse. There’re some people who consider the sexual relations of husband and wife during pregnancy as taboo, even though sexual life is a necessity. This study aims to describe about pregnant womens’ sexual activity perception in Sleman Hospital. This study is descriptive research. Data analysis used univariate analysis. The statistical tests results showed that most pregnant women had sufficient perceptions of 68 (70.83%), 14 (14.58%) of good perceptions, and 14 (14.58%) of less perceptions. The descriptive test results for pregnant women were dominated by ages 21 to 25 years with sufficient perceptions. Pregnant women are dominated by housewives with sufficient perceptions. Parity is predominantly in 1st time pregnancy with sufficient perception. The suggestion is that the research results can be used as a reference and learning material as well as science in midwifery development.